The burden of cancer attributable to dietary dioxins and dioxin-like compounds exposure in China, 2000–2020 - Ziwei Shi; Yiling Li; Xiaohan Song; Yibaina Wang; Jianwen Li; Sheng Wei (Environment International)
Dioxin is a typical class of persistent organic pollutants (POPs) that could cause cancer. In China, the contribution of dietary dioxins to the cancer burden remains underexplored. This study evaluates the cancer risk and burden due to dietary dioxins and dioxin-like compounds among Chinese residents from 2000 to 2020. Based on adjustments in China’s dioxin policies, the study period was divided into three stages with split years of 2007 and 2014 to estimate the toxic equivalent (TEQ) of dioxins. Participants in dietary surveys conducted in 31 provinces were included. Dietary exposure to dioxins was estimated in a probability model and compared with the provisional tolerable monthly intake (PTMI). The risk was assessed using carcinogenic slope factors and expressed as the incremental lifetime cancer risk (ILCR). A two-stage model evaluated the burden of cancer attributable to dietary dioxins and dioxin-like compounds. Among all food categories, the highest concentration of dioxins and dioxin-like compounds was observed in aquatic foods at 0.15 pg TEQ/kg. Median dietary exposure to dioxins among Chinese residents decreased from 12.39 pg TEQ/kg/month to 8.72 pg TEQ/kg/month between 2000 and 2020. Consequently, the ILCR due to dietary dioxins declined from 6.44 × 10-5 to 4.53 × 10-5. The health risks were higher in younger groups and among residents of coastal areas (P < 0.001). The burden of cancer attributable to dietary intake of dioxins and dioxin-like compounds in the Chinese population in 2000–2007, 2008–2014, and 2015–2020 was 2.25 (2.09–2.42) per 100,000, 2.20 (2.06–2.35) per 100,000, and 1.68 (1.60–1.77) per 100,000, respectively. Furthermore, the disease burden was highest for prostate cancer in men and for breast cancer in women. The dioxin management policies has reduced the burden of cancer attributable to dietary exposure to dioxins and dioxin-like compounds in China. However, excess exposure in coastal areas and children remains a priority for attention.